Проблематизація поняття істини в сучасній філософії - Петрушенко, Віктор (Видавництво Львівської політехніки, 2014)
Метою статті є окреслити ті проблемні поля, через сукупність яких окреслюється розуміння істини сучасною філософією. Тут фігурують онтологія істини, зв'язок її з шарами дійсності, зі складовими пізнавального процесу. Доводиться, що аналітика істини має враховувати процесуальний характер істини, складну будову знання та виявлення ролі кожного його компонента в забезпеченні статусу істинності певного конкретного знання, системний характер тих форм, що мають забезпечити формування та функціонування знання. The purpose of the article is to identify a range of problems existing in modern philosophy of truth. The author makes an attempt to identify these problems and classify them according to some reasonable principles. First of all, he addresses the issue of the ontological status of truth, thinking to what sphere of reality truth can be referred, namely material reality (things themselves are true), the sphere of consciousness (truth is a special intellectual formation), the sphere mediating the connection between consciousness and reality (cognition, practice, experience, activity tools), the so-called “third reality” (Plato’s world of ideas or “the world of ideal substances” of K. Popper) or existential living of humans in the world (truth isn’t cognized, we live in it). Besides, the article discloses the reality layers with which truth is connected: the phenomenal world or its essential bases. Finally, the idea that truth is a procedural formation is justified. Truth as a process arises in its dynamic relation towards reality (true knowledge must change because reality itself changes) and the main components of knowledge. The most widespread concepts of truth are presented on the basis of its characteristic examination. The author supports the idea of the truth study through the analysis of the role of the knowledge components (sensory abilities, logical and structural components, notional knowledge components, symbolic forms of its real existence) in asserting its status. All these knowledge components have their true assessment and specific relation to the status of truth. The article explains why truth is often connected with logic and logical accuracy of knowledge.
Problematisation of the concept of truth in modern philosophy
Keywords: істина; істинність; онтологічний статус; процесуальність; системність; truth; verity; reality; ontological status; processuality; systematization